2010
DOI: 10.1590/s0100-84042010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Floral attributes, ornithophily and reproductive success of Palicourea longepedunculata (Rubiaceae), a distylous shrub in southeastern Brazil

Abstract: -(Floral attributes, ornithophily and reproductive success of Palicourea longepedunculata (Rubiaceae), a distylous shrub in southeastern Brazil). Floral attributes, ornithophily and reproductive success of Palicourea longepedunculata Gardner were studied in a fragment of the Atlantic Forest in southeastern Brazil. This species is a distylous shrub that occurs in wet forest understory. In an area of seven hectares, the frequency of the morphs was found at a ratio very close to the expected 1:1. The fl owering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…The greater attractiveness of one floral morph for pollinators may cause an asymmetrical and unidirectional pollen flow (BARRETT, 1992). It is known that the reproductive success of distylous species, including those studied here, depends on the gene flow between floral morphs, whose agents are the pollinators, since illegitimate pollinations normally result in incompatibility (CASTRO et al, 2004;SILVA et al, 2010). One result of this preference for longstyled flowers is the deposition of incompatible pollen, resulting in stigma occlusion, preventing the compatible grains from germinating (GANDERS, 1979), affecting the fruiting of the morph in question.…”
Section: Discussionmentioning
confidence: 99%
“…The greater attractiveness of one floral morph for pollinators may cause an asymmetrical and unidirectional pollen flow (BARRETT, 1992). It is known that the reproductive success of distylous species, including those studied here, depends on the gene flow between floral morphs, whose agents are the pollinators, since illegitimate pollinations normally result in incompatibility (CASTRO et al, 2004;SILVA et al, 2010). One result of this preference for longstyled flowers is the deposition of incompatible pollen, resulting in stigma occlusion, preventing the compatible grains from germinating (GANDERS, 1979), affecting the fruiting of the morph in question.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the reproductive biology of 21 species of Psychotria on Barro Colorado Island, Sakai and Wright (2008) [37] compared data from phylogenetic information of the genus, and found that changes in the morphological characteristics of distyly are associated with the weakening of incompatibility, and monomorphism and homostyly that evolved independently in the genus as a result of low population density and limited availability of pollen. Pollen limitation has been related to the formation of one-seeded fruits in distylous species of Palicourea [38] and Psychotria [20] [39]. The formation of seedless fruits was recorded in Palicourea lassiolaris [40] and P. longepedunculata [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pollen limitation has been related to the formation of one-seeded fruits in distylous species of Palicourea [38] and Psychotria [20] [39]. The formation of seedless fruits was recorded in Palicourea lassiolaris [40] and P. longepedunculata [38].…”
Section: Discussionmentioning
confidence: 99%
“…Espécies do gênero Psychotria e Palicourea produzem frutos carnosos pequenos comumente dispersos por aves (POULIN et al, 1999;FERREIRA & CONSOLARO, 2013). Além disso, considerando que a produção de frutos nas espécies distílicas geralmente depende de polinização intermorfo (GANDERS, 1979), e que o sucesso reprodutivo é afetado pelo dimorfismo floral e proporção equilibrada entre os morfos da população (e.g, SOBREVILA et al, 1983;PEREIRA et al, 2006;KOCH et al, 2010;SILVA et al, 2010), há necessidade de estudos mais detalhados sobre a biologia floral de P. racemosa e de espécies do gênero Palicourea em geral, para o qual têm sido relatados mais casos de homostilia em Rubiaceae (SÁ, 2013).…”
Section: Duração Das Fenofasesunclassified